Breastshot - Loveland, Grace, author; Altschul, Andrew, advisor; Ausubel, Ramona, committee member; MacKenzie, Matt, committee member (Colorado State University. Libraries, 2022)
Breastshot is an exploration of human suffering through the lens of the fantastic. In a series of short, interconnected stories, this novel imagines a world where magic, witches, and gods exist alongside pop stars and fast food burritos. As characters search for meaning in a world that has changed overnight, issues of absurdity and faith are addressed as avenues for exploration and understanding.